(untitled) (London Journal of Medical and Health Research, 2023)
Introduction: The kidney is one of the most frequently injured organs during blunt abdominal trauma, and the probability increases significantly if there is any renal pathology, such as hydronephrosis. The ureter Injury, which is extremely uncommon in blunt trauma, also increases its incidence in the presence of previous renal pathologies. Case report: Patient J.R.A, male, 30 years old, brought to the HMMSJP hemodynamically stable by SIATE after suffering a automobile x truck accident as a driver and the vehicle overturning. A contrast computed tomography (CT) scan of the abdomen, chest and skull CT scan showed a large retroperitoneal collection adjacent to the left kidney, with pelvis distension and a positive “claw sign”. It was concluded that the patient had grade V renal injury, and exploratory laparotomy was indicated. During surgery, a total lesion of the ureter was visualized approximately 10 cm from the ureteropelvic junction (UPJ) with subsequent total left nephrectomy and distal ureter ligation. Discussion: in this case, the patient’s kidney was previously hydronephrotic, due to UPJ stenosis, being more prone to serious injuries in the trauma. There was also ureter injury, which is extremely uncommon in blunt trauma and should be treated as early as possible. Kidney injury should always be suspected in patients with a history of direct impact to the abdomen, with consequent CT scan. Patient management aims at hemodynamic stabilization, preservation of renal tissue and prevention of complications, which can be non-operative, if the injury is low-grade and hemodynamically stable, or surgical, if the injury is high-grade or hemodynamically unstable. Conclusion: Blunt kidney injury is more common in patients with previous renal alterations, while ureteral injuries are mostly due to iatrogenic events during surgery or penetrating trauma, being uncommon in blunt trauma. The correlation between anamnesis, physical examination and imaging tests is essential for the appropriate and individualized management of the patient.